Analysis of CO2 equilibrium solubility of seven tertiary amine solvents using thermodynamic and ANN models. (1st August 2019) - Liu, Helei; Chan, Christine; Tontiwachwuthikul, Paitoon; Idem, Raphael
Abstract: This work investigates the carbon dioxide (CO2 ) equilibrium solubility of seven novel tertiary amines, which include 1-(2-Hydroxyethyl)pyrrolidine (1-(2-HE)PRLD), 4-((2-hydroxyethyl)(ethyl)amino)-2-butanol (HEEAB), 3-diethylamino-1, 2-propanediol (DE-1, 2-PD), 4-(dipropylamino)-2-butanol (DPAB), 1-(2-Hydroxyethyl)-piperidine (1-(2-HE)PP), 4-((2-hydroxyethyl)(methyl)amino)-2-butanol (HEMAB) and 4-(dimethylamino)-2-butanol (DMAB). This analysis study was conducted at the amine concentration of 2.0 mol/L, over the temperature range of 298–333 K, and over the CO2 partial pressure range of 3–101 kPa. Two approaches were adopted in this study. Some thermodynamic models were employed to correlate and predict the experimental results of CO2 equilibrium solubility in the seven novel tertiary amines solution. The new Helei-Liu model and Liu et al. model for K2 correlation were also developed. A comparison of the performances of these models in predicting CO2 solubility showed that the Liu et al. model, which included the significant parameters of temperature, concentration of amine solution, physical solubility of CO2, and total pressure, gave the best performance in predicting CO2 equilibrium solubility in the newly formulated amine solutions. In addition, the artificial neutral network (ANN) approach was adopted for predicting the CO2 equilibrium solubility of the seven tertiary amines. The predicted values of CO2 solubility extracted from the ANN models were compared with those from the thermodynamic models in terms of the absolute average deviation (AAD).